Penerapan Jaminan Kesehatan Terhadap Layanan Keperawatan RSU Daerah - Jamlean, Kayus; Wewra, Gustaf Doland (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
Primary role of nurse is fulfill requirement of basic human needs and to reach satisfaction to own self and also its client. Nurse attitude in giving nursing care will be perceved by patient to favorable and unfavorable. During the time BPJS patient assess about nursing care that had been given was unfavorable of compared to nursing care that had been given to Non JPS patient. And so do Non BPJS patient assess that service of given by nurse was unfaforable. This research was aimed to identify difference perception of BPJS and Non BPJS patient to nursing care in Surgical Room, Piru Hospital. Design used in this research was comparative descriptive study. The population were all BPJS patient and Non BPJS patient in Piru Hospital. Chousy sample were selected by strutified random sampling 15 BPJS and 15 Non BPJS. Risearch instrument used questioner. Data were analyzed by using fisher’s exact test with level of significance of 0,05. Result of this research showed that most BPJS patient had negative perception (80 %), while Non BPJS patient had perception (66,7 %). Through fisher’s exact test showed the existence of difference of perception between BPJS patient and Non BPJS patient to nursing care with value of p = 0,025. It can be concluded that there was difference of perception between BPJS patient and Non BPJS patient to nursing care.